Haemocyte‐mediated immunity in insects: Cells, processes and associated components in the fight against pathogens and parasites. Issue 3 (2nd August 2021) - Eleftherianos, Ioannis; Heryanto, Christa; Bassal, Taha; Zhang, Wei; Tettamanti, Gianluca; Mohamed, Amr
Abstract: The host defence of insects includes a combination of cellular and humoral responses. The cellular arm of the insect innate immune system includes mechanisms that are directly mediated by haemocytes (e.g., phagocytosis, nodulation and encapsulation). In addition, melanization accompanying coagulation, clot formation and wound healing, nodulation and encapsulation processes leads to the formation of cytotoxic redox‐cycling melanin precursors and reactive oxygen and nitrogen species. However, demarcation between cellular and humoral immune reactions as two distinct categories is not straightforward. This is because many humoral factors affect haemocyte functions and haemocytes themselves are an important source of many humoral molecules. There is also a considerable overlap between cellular and humoral immune functions that span from recognition of foreign intruders to clot formation. Here, we review these immune reactions starting with the cellular mechanisms that limit haemolymph loss and participate in wound healing and clot formation and advancing to cellular functions that are critical in restricting pathogen movement and replication. This information is important because it highlights that insect cellular immunity is controlled by a multilayered system, different components of which are activated by different pathogens or during the different stages of the infection. Abstract : Here, we review insect cellular immune mechanisms that limit haemolymph loss and participate in wound healing and clot formation. We also cover haemocyte‐based functions that are critical in restricting pathogen movement and replication.